Modeling and analysis of hyperbolic metamaterials for controlling the spontaneous emission rate and efficiency of quantum emitters - Mota, Achiles Fontana da (2019)
In the past few years, intensive research efforts have been devoted to studying new approaches to controlling the photon emission of quantum emitters (QEs), especially for telecommunication applications. These approaches rely on tailoring the QE\'s radiation, usually assessed via well-known figures-of-merit such as lifetime (τ) and quantum efficiency (η). Controlling the QE\'s photon emission is important because the faster its photons are emitted, the greater is the number of times it returns to the excited state per second. Therefore, it is crucial to create additional decay channels to reduce τ, which necessarily requires increasing the Purcell factor (P). One of the most promising approaches to increase P involves a new class of metamaterials, known as hyperbolic metamaterials (HMM). This class of materials exhibits pronounced anisotropy, with the parallel and perpendicular permittivity tensor elements (with respect to the anisotropy axis) presenting opposite signs, resulting in an open hyperboloidal isofrequency surface (IS). This unusual IS shape leads to the most outstanding feature of HMMs, namely, the existence of photonic modes with wavenumber (k) much larger than those in free-space (k0), known as high-k modes. By engineering these modes, it is possible to manipulate the HMM photonic density of states (PDoS), thus controlling the QE\'s radiation parameters. The simplest approach to designing HMM is by means of a planar stack of alternating thin metal and dielectric layers. However, the finite thickness of these layers induces spatial dispersion, making the extraction of effective parameters (homogenization) of these media a challenging task. In this context, we propose in this thesis a new constitutive parameter retrieval approach that takes spatial dispersion into account for all electromagnetic parameters of the medium. We demonstrate that the real part of the dispersion curve flattens out (correspondingly with a large imaginary part) because of the absence of propagating modes inside the metamaterial. This flat region is strongly dependent on the layer thicknesses and is a direct manifestation of spatial dispersion. Moreover, we demonstrate that the QE\'s lifetime calculation is overestimated if this effect is not taken into account in the homogenization procedure, which is detrimental for telecommunication applications. Moreover, we demonstrate how to enhance P by a factor greater than 100 with the use of HMMs. However, most of the QE dissipated power couples into the HMM as high-k modes (which do not propagate in free-space). Therefore, the energy is thermally dissipated inside the HMM with a consequent reduction of η . Some authors have resorted to nano-patterned HMMs (NPHM) to convert the high-k modes into free-space modes (k≤k0) aiming at increasing η. However, much of the NPHMs designs still rely on computationally costly three dimensional (3D) numerical simulations. Thus, we also propose in this thesis a new semi-analytical method to model, both in two- and three-dimensions (2D and 3D, respectively), the radiation emission of QEs interacting with nano-patterned structures. The low computational cost of this method makes it attractive for mapping P and η as function of the QE and NPHM relative position. This mapping is a helpful tool to understand the decay behavior of the whole system since QEs are arbitrarily distributed and oriented inside the NPHM. The analytically calculated decay curve allows the systems effective quantum efficiency (ηeff) and Purcell factor (Peff) to be directly obtained assuming multiple arbitrarily distributed electromagnetic sources. In this sense, we propose here a new procedure to optimize the NPHM geometrical parameters to maximize ηeff while achieving the desired Peff. We apply the proposed model to an NPHM composed of nine Ag/SiO2 layers, with the polymer host layer embedded with Rhodamine 6G, to maximize ηeff for a specified tenfold increase of Peff. This procedure allowed ηeff to be increased by 69% and 170% for one- and two-dimensional nano-patterning, respectively. Moreover, the time required to build the P and η maps (used in the calculation of the decay behavior) is reduced by approximately 96% when compared to those numerically calculated via FDTD. This procedure paves the way to the realization of new high-speed and efficient light sources for telecommunication applications.